Know thy enemy and know yourself – the role of operational data in managing the mines and booby trap threat in Vietnam, 1965–73 - Evans, Roland; Temple, Tracey; Nelson, Liz (Sage, 2024)
Victim operated explosive devices (VOEDs) such as mines and booby traps, have been an enduring problem since their large-scale use started in the 1940s. While the overall problem is often known about in general terms, the real complexion of the problem was not necessarily fully appreciated. Eventually the need to understand the problem and the response to it was partially identified and acted upon in Vietnam through the collection and analysis of operational data. This did not solve the problem of mines and booby traps, but it did offer a means to better manage the threat.
Keywords: IEDs; landmines; booby-traps; anti-personnel mines; anti-vehicle mines